Hubungan Pemberian ASI dengan Perkembangan Anak Usia 24-36 Bulan Melalui Skrining DDST - Fikri Lutfiatus Sa’adah; Jenie Palupi; Syiska Atik Maryanti (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Based on Riskesdas (2018) coverage of exclusive breastfeeding in Indonesia does not meet the SPM target set by the government which is 80%, coverage in East Java is 40%, in Jember Regency the lowest coverage in Andongsari Health Center is 24.51%, this will affect the scope of child development in the region. East Java Province is targeting 2020 early detection coverage growth of 95% while the current coverage is 53.44%. This study aims to determine the relationship of breastfeeding with the development of children aged 24-36 months through DDST screening in Pontang Village, the working area of Andongsari Health Center, Jember Regency. This type of research is analytic correlation with cross-sectional approach, the population of all mothers who have children aged 24-36 months, obtained a sample of 69 respondents in 6 posyandu with simple random sampling technique. The research instrument was in the form of a questionnaire to assess the history of breastfeeding and a form of DDST to assess progress. Data analysis using chi-square test with SPSS program. The results obtained 51% with a history of non-exclusive breastfeeding, and 49% exclusive breastfeeding. The results of the development assessment were 81% normal, and 19% were suspected. The analysis results obtained p value 0, 241> α (0,05) ie there is no significant relationship between breastfeeding and the development of children aged 24-36 months. Even though the child is given exclusive breastfeeding, child development is not only influenced by breastfeeding, but other internal and external factors can influence.